Pengaruh Literasi Keuangan dan Penerapan Manajemen Risiko terhadap Keberlangsungan UMKM di Kelurahan Tegal Alur - Muhammad Rafli Choirul Umam; Corry Yohana; Rizka Zakiah (Pusat Riset dan Inovasi Nasional, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a role in national development, particularly in strengthening a country's economy, including Indonesia. In addition to contributing to the national economy, MSMEs are one of the sectors with a fairly strong track record in facing the economic crises that have occurred several times in Indonesia. Based on the results of the National Financial Literacy and Inclusion Survey (SNLIK) in 2024, Indonesia's financial literacy index of 65.43% indicates that the public's financial literacy level falls into the moderate category. Therefore, this study aims to examine the relationship between Financial Literacy and Risk Management Implementation on the Sustainability of MSMEs in the Tegal Alur area. The sample was taken using the convenience sampling technique and a quantitative method with secondary data obtained from various reliable sources and primary data from field observations. This study uses a quantitative method with multiple linear regression analysis. The results of the study indicate that partially, financial literacy and risk management have a positive and significant effect on the business sustainability of MSME actors. In other words, when financial literacy and risk management are high, business sustainability will also be high, and vice versa. Furthermore, simultaneously, financial literacy and risk management have a positive and significant effect on business sustainability with a coefficient of determination of 23%, while the remainder is influenced by variables not used and explained in this study.